The Development of Reading Narrative Text Material Based on Local Folklore of the Eleventh Grade Students of SMA Negeri 1 Sinabang - Intan Mahalia; Asnawi; Yulia Arfanti; Harianto II (PT Inovasi Pratama Internasional, 2024)
The objective of study is formulated as follows To know the development of reading narrative text material based on local folklore for the eleventh-grade students of SMA Negeri 1 Sinabang and To know the local folklore in English subject material narrative text effectively used to develop reading learning outcomes for the eleventh- grade of SMA Negeri 1 Sinabang. The type of research used is the Research and Development (R&D) research method. The model used is the ADDIE Model. The ADDIE model is an abbreviation for the five stages of the development process, namely analyze, design, develop, implement, and evaluate. The conclusion of this research are the development of Reading Narrative text by using local folklore was sucessed with the average point of assessment 4,51 that mean the development was at Excellent level. Local folklore as a media to learned reading narrative text, proved success by catagory “effective enough” by the percentage of Ngain score at 60,40% of effectiveness